Construction of ultrasound-responsive urokinase precise controlled-release nanoliposome applied for thrombolysis - Fan, Yongliang; Liu, Li; Li, Fang; Zhou, Hang; Ye, Yizhou; Yuan, Chunping; Shan, Hongli; Zang, Wangfu; Luo, Yu; Yan, Sijing (Frontiers in Bioengineering and Biotechnology, 2022)
Urokinase is widely used in the dissolution of an acute pulmonary embolism due to its high biocatalytic effect. However, how to precisely regulate its dose, avoid the side effects of hemolysis or ineffective thrombolysis caused by too high or too low a dose, and seize the golden time of acute pulmonary embolism are the key factors for its clinical promotion. Therefore, based on the precise design of a molecular structure, an ultrasonic-responsive nanoliposome capsule was prepared in this paper. Singlet oxygen is continuously generated under the interaction of the ultrasonic cavitation effect and the sonosensitizer protoporphyrin, and the generated singlet oxygen will break the thiol acetone bond between the hydrophilic head and the hydrophobic tail of the liposome, and the lipid The body structure disintegrates rapidly, and the urokinase encapsulated inside is rapidly released, down-regulating the expression of fibrinogen in the body, and exerting a thrombolytic function. The in vitro and in vivo results show that the smart urokinase nanoliposomes prepared by us have sensitive and responsive cytocompatibility to ultrasound and good in vivo thrombolytic properties for acute pulmonary embolism, which provides a new strategy for clinical acute pulmonary embolism thrombolysis.